PENGARUH KOMUNIKASI ORGANISASI TERHADAP TEAMWORK ORGANISASI MAHASISWA UNIVERSITAS KH. MUKHTAR SYAFAAT - Lailatul Fadhilah; Abdi Fauji Hadiono (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
Organizing is also one way to train students to develop soft skills and apply their knowledge and in organizational activities students will be accustomed to communicating with others, building cooperation and learning to lead. In the organization in which there are people who have the task of each individual and interconnected with each other as a system that requires good communication to support organizational performance can be achieved. Every member who is in an organization that has a vision, mission or a goal that will be achieved together will run smoothly if communication in the organization goes well. Good communication is that the communicant is able to understand the message to be conveyed by the communicator. Communication has an important role in human life. This role can be seen from the daily activities carried out by each individual. Communication becomes an important condition in establishing relationships with other people. This is because the interaction between individuals can not be separated from the communication itself. This study aims to determine the effect of Organizational Communication on student organization Teamwork. Derived from the condition of students at the University of KH. Mukhtar intercession that follows the organization. Statement from students who follow the organization shows that there is a positive impact in terms of organizational communication, felt after active organization, the researcher is interested in conducting research related to the influence of Organizational Communication on student organization Teamwork. Organizational communication is the sending and receiving of information in a complex organization. Teamwork is a positive synergy through coordinated efforts. The research method used is quantitative research method. Sampling technique using purposive sampling. Sample of 40 respondents. When the study was conducted in May 2024, the research Data were obtained from questionnaires calculated using the help of IBM SPSS 22 for Windows. The results showed that organizational communication has an effect on teamwork with significance value = 0.000 < 0.05, meaning the influence of Organizational Communication on student organization Teamwork. The value of the coefficient of determination test showed that the value of R square as much as 49.1% of the influence of Organizational Communication variables on student organization Teamwork 50.9% influenced by other factors that were not studied. Based on the results of the study, it can be seen that the influence of organizational communication on organizational teamwork of the University of KH. Mukhtar Syafaat.